2022
DOI: 10.1177/11297298221145982
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Valsalva maneuver on pain intensity and hemodynamic status during short peripheral cannula insertion in adults: A systematic review and meta-analysis

Abstract: This systematic review and meta-analysis aimed to summarize the randomized clinical trial studies regarding the effects of Valsalva maneuver on the severity of short peripheral cannula insertion pain and hemodynamic status in adults. A systematic search was conducted on PubMed, Web of Science, Scopus databases, Cochrane, ClinicalTrials.gov, and Google Scholar Search Engine using keywords extracted from Medical Subject Headings, such as “Valsalva Maneuver,” “Valsalva’s Maneuver,” “Forced Expiratory,” “Balloon I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
2
0
4
Order By: Relevance
“…During this maneuver, the vagus nerve is stimulated in connection with baroreceptor activation, and this has an antinociceptive effect (24)(25)(26)(27) . Also, the antinociceptive effect has been explained as occurring through central inhibition relating to the noradrenergic, serotogenic and endogen opioid systems with vagus nerve stimulation (23,28) . On the other hand, it has been reported that another mechanism of the coughing technique depends on the method of directing the attention elsewhere and of diverting the attention so that the person does not feel pain (29) , and that it increases a person's tolerance of pain (23,30) .…”
Section: Introductionmentioning
confidence: 99%
“…During this maneuver, the vagus nerve is stimulated in connection with baroreceptor activation, and this has an antinociceptive effect (24)(25)(26)(27) . Also, the antinociceptive effect has been explained as occurring through central inhibition relating to the noradrenergic, serotogenic and endogen opioid systems with vagus nerve stimulation (23,28) . On the other hand, it has been reported that another mechanism of the coughing technique depends on the method of directing the attention elsewhere and of diverting the attention so that the person does not feel pain (29) , and that it increases a person's tolerance of pain (23,30) .…”
Section: Introductionmentioning
confidence: 99%
“…el dolor al proporcionar un efecto antinociceptivo que funciona en paralelo con los mecanismos de estudio relacionados con la activación de los barorreceptores (20)(21) y la estimulación del nervio vago (23)(24)(25)(26)(27)(28) . También se ha informado que esta técnica es útil en el manejo del dolor ya que se basa en la técnica de desviación de la atención utilizada con mayor frecuencia para controlar el dolor (23,29) .…”
Section: Discussionunclassified
“…Durante esta maniobra, el nervio vago es estimulado en relación con la activación de los barorreceptores, y esto tiene un efecto antinociceptivo (24)(25)(26)(27) . Además, se ha explicado que el efecto antinociceptivo ocurre a través de la inhibición central relacionada con los sistemas opioide noradrenérgico, serotoninérgico y endógeno con la estimulación del nervio vago (23,28) . Por otro lado, se ha informado que otro mecanismo de la técnica de la tos depende del método de dirigir la atención hacia otro lado y de desviar la atención para que la persona no sienta dolor (29) , y que aumenta la tolerancia de la persona a dolor (23,30) .…”
Section: Introductionunclassified
“…Afirma-se na literatura que a técnica da tosse reduz a dor por proporcionar um efeito antinociceptivo trabalhando em paralelo com os mecanismos de estudo relacionados à ativação de barorreceptores (20)(21) e estimulação do nervo vago (23)(24)(25)(26)(27)(28) . Também foi relatado que esta técnica é útil no manejo da dor, pois conta com a técnica de desvio de atenção mais frequentemente usada para controlar a dor (23,29) .…”
Section: Discussionunclassified
“…Durante esta manobra, o nervo vago é estimulado em conexão com a ativação do barorreceptor, e isso tem efeito antinociceptivo (24)(25)(26)(27) . Além disso, o efeito antinociceptivo tem sido explicado como ocorrendo por inibição central relacionada aos sistemas noradrenérgico, serotogênico e opioide endógeno com estimulação do nervo vago (23,28) .…”
Section: Introductionunclassified